TECHNOLOGY FOR PRODUCING A HIGH-QUALITY PRODUCT FROM LOCAL SILK WASTE (Scientific journal of the Fergana State University, 2026)
This scientific work explores the technology for producing a high-quality product from local silk waste. The relevance of the topic is primarily due to the potential for efficient use of raw materials and the economic benefits gained from recycling waste. The study analyzes the compositional characteristics of the waste and proposes advanced methods for its processing. The developed technology is environmentally safe, meets the needs of local industry, and contributes to the creation of new job opportunities. The results of this research are aimed at producing high value-added products based on local raw materials.